Indonesian Intern Teachers in Thailand Classrooms: A Case Study on English Teaching - Siti Nurhafidza; Siswana (Universitas Islam Negeri Palopo, 2026)
This study explores the teaching challenges faced by Indonesian intern teachers during their teaching practicum in Thailand classrooms. Using a qualitative case study approach, data were collected through in-depth interviews with six participants who had completed an international teaching internship program. The findings reveal that language barriers are the most dominant challenge, affecting classroom communication and instructional delivery. In addition, cultural differences, low student motivation, and limited learning media also influence the teaching process. To overcome these challenges, participants applied various strategies such as using simple English, body language, interactive methods like games, and collaboration with local teachers. The study highlights the importance of pedagogical, linguistic, and cultural adaptation in cross-cultural teaching contexts. These findings contribute to a better understanding of international teaching experiences and provide practical insights for preparing future intern teachers.